2015
DOI: 10.1177/0733464815584670
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Influences and BMI in Urban Older Adults

Abstract: Objective Increases in body weight and declining physical activity that may accompany aging are linked to a range of problems affecting daily life (i.e., decreased mobility and overall quality of life). This study investigates the actual and perceived neighborhood environment on overweight and obese urban older adults. Method We selected 217 individuals aged 65+ who answered questions about their neighborhood on the 2009 Speak to Your Health survey. Using multinomial regression models and geospatial models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Fourteen studies examined the relative importance of selected objectively and perceived measured NE attributes on PA in general [ 120 , 122 , 123 , 129 , 133 – 142 ] and four studies investigated associations between attributes of the NE and specific PA or walking domains [ 40 , 121 , 124 , 127 ]. Some studies aimed to explore the relationships between different NE attributes and PA in a specific population group, for example in adults with type 2 diabetes [ 119 ], kidney cancer survivors [ 128 ] or overweight and obese urban older adults [ 143 ]. One quarter of the studies (n = 9) tested the mediating role of demographic, psychosocial, functional, behavioral, and/or environmental features on the association between NE and PA [ 125 , 127 , 128 , 130 132 , 144 146 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies examined the relative importance of selected objectively and perceived measured NE attributes on PA in general [ 120 , 122 , 123 , 129 , 133 – 142 ] and four studies investigated associations between attributes of the NE and specific PA or walking domains [ 40 , 121 , 124 , 127 ]. Some studies aimed to explore the relationships between different NE attributes and PA in a specific population group, for example in adults with type 2 diabetes [ 119 ], kidney cancer survivors [ 128 ] or overweight and obese urban older adults [ 143 ]. One quarter of the studies (n = 9) tested the mediating role of demographic, psychosocial, functional, behavioral, and/or environmental features on the association between NE and PA [ 125 , 127 , 128 , 130 132 , 144 146 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no previous study has examined the association between the perceived proximity of exercise facilities and CVD risk, although research on other health outcomes has produced similar findings to the associations seen among men in this study. For example, Auchincloss et al [ 43 ] found that neighborhood physical activity resources were associated with a lower hazard ratio for diabetes (0.65) in the U.S. Mathis et al [ 44 ] investigated the association between BMI and local recreational facilities and showed that obese older adults had a significantly lower probability of having a park in their neighborhood. Previous research has also highlighted the ways in which such an environment might be beneficial for health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, neighborhood safety (defined as being able to walk safely during the day and at night, crime and violence) has also been linked to the cardiovascular health (CVH) score, a concept recently introduced by the American Heart Association [ 1 ]. The perceived risk of traffic accidents and reduced personal safety have also been associated with other health indicators such as obesity [ 21 , 44 ], mental well-being [ 45 47 ] and physical functioning [ 47 ]. Living in fear might result in more time being spent indoors, lower levels of physical activity, and higher levels of psychological stress, all of which have the possibility to impact on CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessed the relationship between neighborhood crime and obesity using objective crime data, which were drawn from a number of different sources including state and local law enforcement agencies [54-56, 53•, 57] and the Federal Bureau of Investigation (FBI) [58]. For instance, one longitudinal study examined associations between crime rate and obesity among young adults over time [54].…”
Section: The Role Of Neighborhood Social Environment Factors In Pa Anmentioning
confidence: 99%